EFFECTIVENESS OF WORK MOTIVATION AND EMPLOYEE ABILITIES TO THE DISTRICT LOCAL GOVERNMENT ORGANIZATION GIVE IT GORONTALUS - Syamsu Qamar Badu; Novianty Djafri (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
A government organization has a predetermined purpose. Success in achieving these goals is not only from government operational funds, facilities and infrastructure, and technology, but depends on human resources. Therefore, this study aims to see the influence of work motivation and employee ability on the effectiveness of local government organizations, with the hypothesis that